The influence of concomitant proton pump inhibitors use on treatment efficacy in hepatocellular carcinoma patients receiving immune checkpoint inhibitors: a systematic review and meta-analysis - Duan, Yangfei; Zhao, Qitai; Feng, Shumin; Jing, Wei; Wang, Dan; Zhang, Yi (Frontiers in Immunology, 2026)
BackgroundDespite the significant survival benefit offered by immune checkpoint inhibitors (ICIs) in patients with hepatocellular carcinoma (HCC), a subset of patients still develop drug resistance. Recent evidence suggests that proton pump inhibitors (PPIs) may influence the therapeutic efficacy of ICIs, but the clinical relevance of this interaction remains unclear. This meta-analysis aims to systematically evaluate the association between concomitant PPIs use and clinical outcomes in HCC patients receiving ICIs therapy.MethodsA comprehensive search of the PubMed, Embase (via Ovid), and Web of Science databases was conducted to identify relevant studies published before May 14, 2025. The primary endpoints of the meta-analysis were overall survival (OS) and progression-free survival (PFS).ResultsFive retrospective studies comprising a total of 1,257 patients were included, of whom 606 (48.2%) received PPIs concurrently with ICIs. The meta-analysis showed no statistically significant association between PPIs use and either OS (HR: 1.04, 95% CI: 0.88-1.24, P = 0.64) or PFS (HR: 0.92, 95% CI: 0.74-1.14, P = 0.44). These findings were further supported by a Bayesian sensitivity analysis performed to address the uncertainty inherent in a limited number of studies.ConclusionBased on the current evidence from retrospective studies, concomitant use of PPIs does not appear to significantly affect survival outcomes in HCC patients treated with ICIs. However, given the inherent limitations of the included studies, this conclusion should be interpreted with caution and warrants validation through prospective investigations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251026028, CRD420251026028.